Coordination, differentiation and the timing of radio commercials - Andrew Sweeting (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
This paper examines whether commercial radio stations try to play their commercials at the same time. A simple model shows that stations may want to choose the same times (coordination) or different times (differentiation) depending on how listeners behave. It also shows that how much commercials overlap in equilibrium should vary with observable market characteristics, such as the number of stations, and that how these characteristics affect equilibrium overlap should depend on whether stations want to coordinate or differentiate. Panel data on the timing of commercials by 1,094 contemporary music radio stations in 147 metro-markets provides consistent support for the version of the model where stations want to coordinate on timing with commercials overlapping more in markets with fewer stations, less listening to out-of-market stations, more concentrated ownership and more asymmetric distributions of listenership across stations.
Keywords: 330; Rundfunkwerbung; Zeitökonomik; Theorie; USA; Koordination